The structure of mouse L1210 dihydrofolate reductase-drug complexes and the construction of a model of human enzyme. - Stammers, D; Champness, J; Beddell, C; Dann, J; Eliopoulos, E; Geddes, A; Ogg, D; North, A (1987)
The structure of mouse L1210 dihydrofolate reductase (DHFR) complexed with NADPH and trimethoprim has been refined at 2.0 A resolution. The analogous complex with NADPH and methotrexate has been refined at 2.5 A resolution. These structures reveal for the first time details of drug interactions with a mammalian DHFR, which are compared with those observed from previous X-ray investigations of DHFR/inhibitor complexes. The refined L1210 structure has been used as the basis for the construction of a model of the human enzyme. There are only twenty-one sequence differences between mouse L1210 and human DHFRs, and all but two of these are located close to the molecular surface: a strong indication that the active sites are essentially identical in these two mammalian enzymes.